The gut microbiota urolithin metabotypes revisited: the human metabolism of ellagic acid is mainly determined by aging. Issue 8 (13th July 2018) - Cortés-Martín, A.; García-Villalba, R.; González-Sarrías, A.; Romo-Vaquero, M.; Loria-Kohen, V.; Ramírez-de-Molina, A.; Tomás-Barberán, F. A.; Selma, M. V.; Espín, J. C.
Abstract : Human urolithin gut microbiota metabotypes are mainly determined by aging. Abstract : Understanding individuals' response to dietary bioactives is crucial for personalized nutrition. We report here for the first time in a Caucasian cohort (5–90 years, n = 839) that aging is the main factor that determines the gut microbiota involved in the ellagic acid–ellagitannin metabolism (urolithin metabotypes), with potential consequences for human health.